Synthesis of Alginate/Hydroxyapatite Beads for Acetaminophen Delivery - Angan, Anesylvia; Sambudi, Nonni Soraya (Makara Journal of Science, 2022)
Conventional drug delivery systems usually involve the intake of multiple drugs, which could amplify the risk of overdosing. Acetaminophen is a widely used pain relief substance that is prone to accidental overdosing. Hence, a controlled drug delivery system is needed to ensure its efficacy. A nanocomposite hydroxyapatite/alginate system that was used as a drug carrier for acetaminophen was synthesized through the sol-gel method, and the mechanism underlying its controlled drug delivery was investigated. Spherical nanocomposite bead samples were synthesized by incorporating 5 wt%, 10 wt%, and 15 wt% hydroxyapatite into mixtures containing alginate. The mixtures were then dropped into calcium chloride solution. The phase purity of the hydroxyapatite sample was confirmed through X-ray diffraction, and the functional groups that confirmed the presence of alginate and hydroxyapatite in the nanocomposite samples were analyzed by using Fourier transform infrared spectroscopy. The release of acetaminophen can be controlled for 48 h, and the Korsmeyer–Peppas kinetics model showed the best correlation for all samples. The kinetics of Al/HAp5, Al/HAp10, and Al/HAp15 were governed by quasi-Fickian diffusion with the n values of 0.199, 0.238, and 0.225, respectively. The composite beads show potential for application as a controlled drug delivery vehicle.